THE EFFECT OF MURABAHAH MARGINS AND MURABAHAH FINANCING ON PROFITS AT PT. SHARIA PEOPLE'S FINANCING BANK (BPRS) SINDANGLAYA KOTANOPAN - sunarji harahap; erni erni; maisarah maisarah (Institut Agama Islam Negeri Padangsidimpuan, 2022)
The background in this research is the existence of a phenomenon that is not in accordance with the theory that if the financing channel increases it will affect the bank’s profit, but seen from the data not in accordance with the theory. The formulation of the problem in this study is whether Murabaha margins and Murabaha financing have an influence on earnings partially or simultaneously, the purpose of this study of Murabaha margins and Murabaha financing on earnings at PT. Rakyat Syariah Financing Bank (SRB) Sindanglayan Kotanopan. The study discusses the effect of Murabaha margins and Murabaha financing PT Syariah Sindanglaya People’s Financing Bank Kotanopan so that the theory and theory of the Qur’an are adjusted to the scope, we can see how it affects the Sindanglaya Kotanopan Sharia People Financing Agency. This research is a quantitative study using secondary data with a sample of 48 samples with a saturated sampling design. Data collection techniques used are documentation and study of literature. data obtained from the financial ratio report of the Islamic Peoples’ Financing Bank Sindanglaya Kotanopan Published by the authority. Data analysis techniques using multiple linear regression data processed by computer SPSS Persi 22. The result of the study showed that the R test was influential by 64,5% while 35,5% was influenced by other variables. The result of the t-test hypothesis showed that tarithmetic ttable ( 8,657 2,01410) and Murabaha financing had an influence on the profit tatitmetic ttable (2,223 2,01410). Simultaneously Murabaha margin and Murabaha financing affect profit because of Fcalculate Ftable (40,843 3,20). This means Murabaha margins and financing margins have a positive effect on earnings.